The Importance Of Principal Leadership In Curriculum Transformation - Yani Yani; Asep Herry Hernawan (At-Tarbiyat, 2024)
The curriculum will always change and be updated from time to time, this happens because of the development of technology, communication, culture, and science which also updates the needs of individuals and society. However, this curriculum update will not be useful if the school cannot or fails to implement it, therefore the role of educators and education personnel is very important, especially the role of the principal who is the leader of a school itself. This study aims to raise the focus of the Importance of Principal Leadership in Implementing the New Curriculum to then become a source of information for all parties, especially those interested and in the field of education, especially candidates and principals. The method used in this research uses a qualitative method with a literature study approach, data obtained from books, journals and other reading materials relevant to this research. After the data is obtained, the data is analyzed by filtering the data according to its type after which the analysis is carried out to obtain conclusions according to what it is. The results of this study indicate that through visionary, strategic leadership, and paying attention to the needs of all stakeholders, principals can lead schools to success in adopting and implementing curriculum changes that can improve the quality of education and student learning outcomes, otherwise if the principal's leadership is poor, it will result in chaos in the implementation of the curriculum which is reflected through the learning process carried out by teachers.